Analyzing Qualitative Data - Ilene Harris (Association of American Medical Colleges, 2006)
Abstract Qualitative data is increasingly used in medical education for needs assessments, program development, curriculum evaluation, performance assessment, and various scholarship applications. This PowerPoint presentation outlines the uses of qualitative data, the context of its use, definitions, forms of data collection, procedures for analysis with attention to trustworthiness, approaches for display of results, issues in analysis, and recommended references. Detailed examples illustrate the nature of qualitative data and methods for its analysis. This work may be used in a workshop or for independent study. If used in a workshop, it is useful to begin with introductions and a discussion of participants' use of qualitative data. The presentation should be interactive and discussion-based. At the end it is useful for participants to practice analyzing a small qualitative data set (e.g., responses to open-ended survey questions), and then to discuss the themes identified and the experience of analyzing the data set. This presentation is the central component in workshops which have been given many times at the AAMC annual meeting, the International Association of Medical Science Educators annual meeting, and the Fellows' Institute for the Foundation for the Advancement of Medical Education and Research (FAIMER).